Risk Factors for Primary Middle East Respiratory Syndrome Coronavirus Infection in Camel Workers in Qatar During 2013–2014: A Case-Control Study - Sikkema, Reina S.; Farag, Elmoubasher A. B. A.; Himatt, Sayed; Ibrahim, Adel K.; Al-Romaihi, Hamad; A. Al-Marri, Salih; Al-Thani, Mohamed; El-Sayed, Ahmed M.; Al-Hajri, Mohammed; L. Haagmans, Bart; Koopmans, Marion P. G.; Reusken, Chantal B. E. M. (The Journal of infectious diseases, 2017)
The transmission routes and risk factors for zoonotic Middle East respiratory syndrome coronavirus (MERS-CoV) infections are still unknown. We used the World Health Organization questionnaire for MERS-CoV case-control studies to assess risk factors for human MERS-CoV seropositivity at a farm complex in Qatar. Nine camel workers with MERS-CoV antibodies and 43 workers without antibodies were included. Some camel-related activities may pose a higher risk of MERS-CoV infection, as may cross-border movements of camels, poor hand hygiene, and overnight hospital stays with respiratory complaints. The risk factors identified in this study can be used to develop infection prevention and control measures for human MERS-CoV infections.